Accounting treatment for corporate zakat: a critical review - Muhammad Akhyar Adnan, Nur Barizah Abu Bakarning Institute Islamic Development (Emerald, 2009)
Purpose – The purpose of this paper is to review the accounting treatments for corporate zakat, as advocated by accounting standards and guidelines, as well as those been practised by relevant corporations. The aim is to determine their appropriateness and adherence to both the Islamic as well as the accounting theoretical perspectives. Design/methodology/approach – Accounting standards and guidelines related to zakat, including the Financial Accounting Standard No. 9 and the Technical Release i-1, are examined. Additionally, analyses are made on the practices of Islamic financial institutions to determine their compliance with both standards and ontological aspects of zakat. Findings – The study reveals that there is a general misconception of zakat, as indicated in several standards and guidelines, which has consequently resulted in inappropriateness in their proposed corporate zakat recognition and measurement and hence presentations. These inaccuracies, in one way or another, have not been in line with the true spirit of zakat in Islam. More worryingly, some unfavorable consequences may and in fact have already been implicated on the larger Muslim community as a result. Research limitations/implications – An alternative view on the accounting treatment of corporate zakat is offered in this paper with the aim to provide a fair and proper assessment of zakat on corporate wealth, which is more parallel to the true spirit of zakat. Originality/value – The paper integrates both the revealed and the contemporary accounting knowledge in scrutinizing the standards and practices as well as in recommending an improved and meaningful alternative.